KEDUDUKAN PEREMPUAN DALAM PERKAWINAN (Analisis UU RI. No. 1 tahun 1974 Tentang Posisi Perempuan) - Saidah Saidah (AL-MAIYYAH : Media Transformasi Gender dalam Paradigma Sosial Keagamaan, 2017)
This paper attempts to highlight the existence of Law No. 1 of 1974 on Marriage which is gender biased. The position of the husband as the head of the household (leader) has the responsibility of living for his family, so that their duty is in the public sphere while the wife is a housewife serving in the domestic sphere, taking care of the child and husband, which is considered to imprison women's space into the public space. The position of women in Islamic marriage law can be seen on several sides, ie women in the Qur'an and Hadith, in history and in the book of fiqh.